Interactions among nitrogen fixation and soil phosphorus acquisition strategies in lowland tropical rain forests. (28th July 2014) - Nasto, Megan K.; Alvarez‐Clare, Silvia; Lekberg, Ylva; Sullivan, Benjamin W.; Townsend, Alan R.; Cleveland, Cory C.; Johnson, Nancy
Abstract Paradoxically, symbiotic dinitrogen (N2) fixers are abundant in nitrogen (N)‐rich, phosphorus (P)‐poor lowland tropical rain forests. One hypothesis to explain this pattern states that N2 fixers have an advantage in acquiring soil P by producing more N‐rich enzymes (phosphatases) that mineralise organic P than non‐N2 fixers. We assessed soil and root phosphatase activity between fixers and non‐fixers in two lowland tropical rain forest sites, but also addressed the hypothesis that arbuscular mycorrhizal (AM) colonisation (another P acquisition strategy) is greater on fixers than non‐fixers. Root phosphatase activity and AM colonisation were higher for fixers than non‐fixers, and strong correlations between AM colonisation and N2 fixation at both sites suggest that the N–P interactions mediated by fixers may generally apply across tropical forests. We suggest that phosphatase enzymes and AM fungi enhance the capacity of N2 fixers to acquire soil P, thus contributing to their high abundance in tropical forests.